Isolation and molecular phenotypic identification of fungi associated with rotting palm fruits - Kadhim, Muntaha J.; Fayyadh, Mohammed A; Salih , Yehya A. (Basrah Journal Of Date Palm Research, 2023)
A study was conducted at the College of Agriculture, University of Basrah, plant protection Department, with the aim was to isolate and identify fungi from fungi cultivars of dates. The results showed the isolation of several fungi from date palm fruit samples of different cultivars that were collected from different regions of Basrah Governorate, The results of the study showed that several types of fungi were isolated in general for the fruit rot disease of the date palm, for the new stages (Khalal, Tartib, and Tamr), and for seven different varieties: Barhi Barim, Al-Halawi, Al-Khadrawi, Al-Zahidi, Al-Dairi, and Al-Sayer. and isolation of several fungi from date palm fruit samples of different varieties that were collected from different regions of Basrah Governorate, the most important of which are Aspergillus flavus, A. parasticus, A. niger, Alternaria alternata, Cladosporium spp., Curvularia lunata, Penicillium spp., and Rhizopus spp..The results of the molecular diagnosis showed that the most important fungi isolated were Aspergillus flavus, Aspergillus niger, Aspergillus parasticus, and A. alternata. The nucleotide sequences of the identified species were recorded in GenBank under the sequence LC752801.1, Op602315.1, LC752805.1, LC752802.1, and LC752803.1 for A. flavus, A.niger, A.parasticus, and A.alternata Cheatomium globosum, respectively. The results showed that there was a match between the mentioned fungal species and the species registered in the NCBI GenBank, with a percentage ranging between 100-99%.